2015
DOI: 10.1016/j.synthmet.2015.08.031
|View full text |Cite
|
Sign up to set email alerts
|

ToF-SIMS characterization of silk fibroin and polypyrrole composite actuators

Abstract: A B S T R A C TBiocompatible materials capable of controlled actuation under biologically relevant conditions are in high demand for use in a number of biomedical applications. Recently, we demonstrated that a composite material composed of silk biopolymer and the conducting polymer polypyrrole can bend under an applied voltage using a simple bilayer device. Here, further characterization of these bilayer actuators using time-of-flight secondary ion mass spectrometry is presented. The roles of different electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Conducting polymers can be used in actuation, but as these materials are often brittle, fillers are often used to improve the mechanical properties. As an example, Bradshaw et al designed actuators based on interpenetrating networks of polypyrrole (PPy) and silk fibroin, 130 a system of potential viability for in vivo applications. They used ToF‐SIMS depth profiling to examine changes in both dopant and ion concentration after actuation in phosphate buffered saline (which contains both phosphate and chloride ions).…”
Section: Polymer Compositesmentioning
confidence: 99%
“…Conducting polymers can be used in actuation, but as these materials are often brittle, fillers are often used to improve the mechanical properties. As an example, Bradshaw et al designed actuators based on interpenetrating networks of polypyrrole (PPy) and silk fibroin, 130 a system of potential viability for in vivo applications. They used ToF‐SIMS depth profiling to examine changes in both dopant and ion concentration after actuation in phosphate buffered saline (which contains both phosphate and chloride ions).…”
Section: Polymer Compositesmentioning
confidence: 99%
“…In all reactions, para-toluenesulfonic acid (pTSA) was added to serve as a small molecule dopant, as previous studies found pTSA to be an effective and stable dopant for our silk-PPy composites [19]. Polymerizations initiated with FeCl 3 in the presence of pTSA result in doping with both chloride and tosylate [29], therefore polymerizations employing Fe(OTs) 3 were also investigated to produce polymers with tosylate anions as the sole dopant [30]. These larger organic acids are trapped in the PPy matrix more effectively than chloride ions, and typically give rise to more stable, conductive materials [31,32].…”
Section: Synthesis and Characterization Of Silk-ppy Compositesmentioning
confidence: 99%
“…While not significantly different than the 1:1 pyrrole:FeCl 3 films, the Fe(OTs) 3 films were slightly more stable over time, likely due to diminished dopant leaching [31,32] as these films have tosylate anions as the sole dopant. Films synthesized with FeCl 3 retain some chloride ions [29], which are more mobile than tosylate and can readily leach and de-dope the polymer matrix over time. Given this information, more extensive washing prior to use to extract the bulk of the unbound ions, followed by dry long-term storage would be recommended for devices intended for implantation.…”
Section: Synthesis and Characterization Of Silk-ppy Compositesmentioning
confidence: 99%
“…Previously, our group developed strategies for incorporating conductive PPy into silk structures to form a completely integrated interpenetrating network (IPN) of silk and PPy, and demonstrated their use as electromechanical bilayer bending actuators . These silk‐PPy bilayer actuators were capable of generating stresses comparable to human muscle (>0.1 MPa) and were electrochemically stable .…”
Section: Introductionmentioning
confidence: 99%